2010
DOI: 10.1016/j.juro.2009.08.160
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Durability of Percutaneous Tibial Nerve Stimulation for the Treatment of Overactive Bladder

Abstract: Statistically significant overactive bladder symptom improvement achieved with 12 weekly percutaneous tibial nerve stimulation treatments demonstrates excellent durability through 12 months. The durability of response demonstrates the effectiveness of percutaneous tibial nerve stimulation as a viable, long-term therapy for overactive bladder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
120
0
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(127 citation statements)
references
References 20 publications
2
120
0
5
Order By: Relevance
“…Urge incontinence episodes per day decreased from 3/day at baseline to 0.3/day at 12 weeks vs. 1.8/ day at baseline to 1.0/day for sham (p<0.001). [19] In a randomized, controlled study, Finazzi-Agro et al [17] reported that PTNS significantly increased voided volume than sham treatment (150-186 mL in the PTNS treatment group vs. 146-150 mL in the sham group, p<0.001). In a urodynamic study, Klingler et al [21] reported that PTNS increased the mean total bladder capacity from 197 mL at baseline (range 35-349 mL) to 252 mL (range 78-384 mL, p<0.01) after 12 weeks of therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Urge incontinence episodes per day decreased from 3/day at baseline to 0.3/day at 12 weeks vs. 1.8/ day at baseline to 1.0/day for sham (p<0.001). [19] In a randomized, controlled study, Finazzi-Agro et al [17] reported that PTNS significantly increased voided volume than sham treatment (150-186 mL in the PTNS treatment group vs. 146-150 mL in the sham group, p<0.001). In a urodynamic study, Klingler et al [21] reported that PTNS increased the mean total bladder capacity from 197 mL at baseline (range 35-349 mL) to 252 mL (range 78-384 mL, p<0.01) after 12 weeks of therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The earliest ones are case series or single-arm efficacy studies, [14][15][16] three are randomized, controlled trials, [9,17,18] and two are long-term follow-up studies of patients who were responders in the overactive bladder innovative therapy (OrBIT) and sham effectiveness in the treatment of overactive bladder symptoms (SUmiT) trials. [19,20] Over half of the patients receiving PTNS therapy in the SUmiT trial, a randomized, double-blinded, sham controlled study, reported moderate or marked improvement in bladder symptoms (54.5% in PTNS patients vs. 20.9% in sham, p<0.001). In addition, PTNS reduced the number of voids per day from 12.3 at baseline to 9.8 …”
Section: Discussionmentioning
confidence: 99%
“…Thus, it will be necessary to explore more information on long-term therapy. 19 Macdiarmid et al 45 evaluated the durability in long-term of PTNS in OAB by the continuation of the second phase of the overactive bladder innovative therapy trial (OrBIT) where 33 responders of the PTNS group received an additional nine months of PTNS treatment. There was significant (statistically) improvement of OAB symptoms with 12 weekly PTNS that demonstrated good durability of 12 months through.…”
Section: 44mentioning
confidence: 99%
“…This conclusion was obtained from 12 months mean improvements from the baseline in frequency, urge incontinence, nocturia, and voided. 45 In addition, there was sustained therapeutic effects of PTNS (STEP) study which was the continuation from Study of Urgent PC versus Sham Effectiveness in Treatment of Overactive Bladder Symptoms (SuMIT) evaluating long-term efficacy of PTNS. After successful 12 weekly treatments, patients continued with 14-week tapering protocol and personalized treatment plan.…”
Section: 44mentioning
confidence: 99%
“…[5][6][7][8] Improvement in bladder function was assessed by using either patient's own record of fluid intake, urine output and leaks (voiding diary), cystometrogram (CMG) or quality-of-life questionnaires. 5,6,8,9 In a multi-center study conducted using PTN stimulation by Govier et al, 3 urodynamics was used at the time of screening the patient for detrusor overactivity, the analyses of the results were based on voiding diary and quality of life questionnaire. They observed a 71% treatment success rate by considering multiple parameters such as reduction in voiding frequency, urge incontinence, improvement in quality of life and improvement in pain.…”
Section: Introductionmentioning
confidence: 99%